Patient-reported outcomes with direct-acting antivirals for the treatment of chronic hepatitis C: current knowledge and outstanding issues. (4th March 2017) - Marcellin, Fabienne; Roux, Perrine; Protopopescu, Camelia; Duracinsky, Martin; Spire, Bruno; Carrieri, Maria Patrizia
ABSTRACT: Introduction : Patient-reported outcomes (PROs) play a key role in the evaluation of direct-acting antivirals (DAA) for the treatment of chronic hepatitis C (CHC). The main PROs of particular interest in CHC include quality of life (QoL), fatigue and its functional repercussions, work productivity, adherence to treatment, and risk behaviors. Areas covered : This study summarizes the body of knowledge regarding PROs in CHC with DAA-based therapy. Outstanding related issues are presented and discussed. Expert commentary : Current knowledge on PROs with CHC mainly relies on clinical trial data. All-oral DAA regimens are associated with minimal QoL impairment and symptom burden, rapid recovery once treatment has ended, and improvement in PROs for a non-negligible proportion of treated patients, especially HCV clearers. Further research is needed to analyze both long-term changes in PROs, and PROs in specific populations including people who use drugs, comorbid patients and patients at risk of reinfection.